Design and Build of 1000 V Joule Thief Inverter by Utilizing Pineapple as an Energy Source - Wiwin A Oktaviani; Arrofi Maulana (Journal of Robotics and Control (JRC), 2022)
The availability of fossil energy-based energy sources is currently depleting and cannot meet the increasing consumption. Therefore, the development of environmentally friendly alternative energy or known as green energy is increasingly being encouraged. One form of green energy that can be utilized, especially in the South Sumatra region, is pineapple. In this paper, the use of pineapple as a raw material for batteries is introduced. The material for making pineapple batteries will affect the amount of battery capacity produced. The pineapple battery capacity will then determine the amount of output voltage generated by the joule thief converter. Apart from the material, the voltage increase in the joule thief converter circuit is also influenced by the source voltage of the pineapple battery, the ferrite core step-up transformer, and the arrangement of the diodes and capacitors in the circuit. The pineapple battery capacity produced in this study is 1209 mAh, the maximum voltage is 4.63 V, the pineapple battery life is 1.0334 hours, and the charging process is 34 minutes. The resulting circuit in this study shows that the maximum output voltage of the joule thief converter is 1531 V, a current of 4.19 mA and the ability to increase the voltage to the source is 300 times.